2014
DOI: 10.1002/jez.1865
|View full text |Cite
|
Sign up to set email alerts
|

The role of fore‐ and hindlimbs during jumping in the Dybowski's frog (Rana dybowskii)

Abstract: Anurans are well known for their jumping abilities, making use of their strong hindlimbs. In contrast, the function of the forelimbs during take-off has rarely been studied. We measured the ground reaction forces exerted by forelimbs and hindlimbs during short jumps in the Dybowski's frog Rana dybowskii. Take-off occurred in two phases. Phase one (from the initial time until the forelimbs took off), which lasts a relatively long time (63.2 ± 4.1% of the total take-off phase, N = 20), provides sufficient time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Peak vertical force both exceeded and occurred earlier than peak horizontal force in K. maculata, similar to ranids Nauwelaerts and Aerts, 2006;Astley and Roberts, 2014;Wang et al, 2014) but unlike hylids . Maximum take-off velocities in K. maculata were slightly below average velocity reported in other frogs, whereas jump distance (scaled to SVL) was within the range reported for ranids but substantially lower than distances recorded in hylids ( Table 4).…”
Section: Moment Arms and Kinematics Influence Jump Angle In K Maculatamentioning
confidence: 63%
See 1 more Smart Citation
“…Peak vertical force both exceeded and occurred earlier than peak horizontal force in K. maculata, similar to ranids Nauwelaerts and Aerts, 2006;Astley and Roberts, 2014;Wang et al, 2014) but unlike hylids . Maximum take-off velocities in K. maculata were slightly below average velocity reported in other frogs, whereas jump distance (scaled to SVL) was within the range reported for ranids but substantially lower than distances recorded in hylids ( Table 4).…”
Section: Moment Arms and Kinematics Influence Jump Angle In K Maculatamentioning
confidence: 63%
“…Maximum take-off velocities in K. maculata were slightly below average velocity reported in other frogs, whereas jump distance (scaled to SVL) was within the range reported for ranids but substantially lower than distances recorded in hylids ( Table 4). The proximal to distal pattern of joint opening observed during jumping in K. maculata has been widely reported among frogs Peters et al, 1996;Nauwelaerts and Aerts, 2003;Astley and Roberts, 2014;Wang et al, 2014) and is thought to maximize foot-to-ground contact time, prolong acceleration (so that maximum velocity is reached as late as possible) and aid in elastic energy pre-storage (Bobbert and van Ingen Schenau, 1988;van Ingen Schenau, 1989;Wang et al, 2014). Range of movement and maximum values of extension for the ankle, knee, hip and sacroiliac joints in K. maculata are similar to those reported in other species Peters et al, 1996;Nauwelaerts and Aerts, 2003;Astley and Roberts, 2014).…”
Section: Moment Arms and Kinematics Influence Jump Angle In K Maculatamentioning
confidence: 87%
“…After the onset of body motion, jumps proceeded in two phases: a slow 'preparatory' phase followed by a fast 'launch' phase. Similar to ranid frogs, the preparatory phase (roughly first ∼60-80% of duration) is marked both by forelimb contact (Wang et al, 2014) and slow acceleration of the COM (Fig. 4).…”
Section: Inverse Kinematics Predictions Of Joint Functionmentioning
confidence: 81%
“…The present study addressed how frog joint kinematics shift to enable flexibility of jump angles. Because prior work found that forelimb preparation angle predicts take-off angle (Wang et al, 2014), we hypothesized an analogous 'joint preparation angle' whereby leg joints form a '3D extension plane' whose inclination is preset to determine final take-off angle (ψ take-off ; Fig. 1).…”
Section: Inverse Kinematics Predictions Of Joint Functionmentioning
confidence: 99%
See 1 more Smart Citation